Management ship operation for maritime schools - Ventosa, Florencio J.T. (Metro Manila : National Book Store, INC., 1994)
When compiling this book, the underlying thought was to afford a good opportunity of getting an insight into matters relating to the operations and management of vessel from the shipowners point of view.
Chapter 1. Introduction -- Chapter 2. Sea transport costs and evaluation of freight rates -- Chapter 3. Distribution and disposition of cargo: Stability -- Chapter 4. Seaworthiness in relation to the safe carriage of cargo -- Chapter 5. Ventilation of cargo -- Chapter 6. Pilferage: Broaching cargo -- Chapter 7. Receiving/ Delivering cargo -- Chapter 8. The ton and tonnage -- Chapter 9. Stowage factor and stowage plans -- Chapter 10. Port statistics.
Keywords: MANAGEMENT -- MARITIME